Patient Recovery from COVID-19 Infections: Follow-Up of Hair, Nail, and Cutaneous Manifestations - Rattapon Thuangtong (2022)
Background. COVID-19 is a pandemic disease worldwide. Although cutaneous manifestations may present in affected patients, there have been limited studies on the cutaneous findings and hair and nail abnormalities after discharge. Objective. To establish the cutaneous manifestations, hair and scalp disorders, and nail abnormalities in patients who recovered from COVID-19 infections. Methods. A retrospective chart review and telephone interviews were conducted to determine the cutaneous manifestations, hair and scalp disorders, and nail abnormalities of patients aged over 18 years who were diagnosed with COVID-19 infections at Siriraj Hospital, Bangkok, Thailand, between January and June 2020. Results. Ninety-three patients with prior COVID-19 infections participated in the study. The COVID-19 severity had been mild for most (71%). Cutaneous manifestations were reported in 8 patients (8.6%), with the common skin conditions being maculopapular rash and urticaria. The onsets of the skin conditions were before admission (1%), during admission (4.3%), and after discharge (3.2%). Increased hair shedding was also reported in 22 patients (23.7%), with a female predominance. Three patients were affected during admission, while the others were affected after discharge. The patients with moderate, severe, and critical COVID-19 infections experienced significantly more hair shedding than those with asymptomatic and mild diseases. Only 2 patients with mild COVID-19 disease reported nail abnormalities (chromonychia and brittle nails). Conclusions. Cutaneous manifestations, hair disorders, and nail abnormalities can occur in patients with COVID-19 after their discharge from hospital. Patients should therefore be followed up in anticipation of dermatological problems.